Encapsulation of Lactiplantibacillus plantarum and Beetroot Extract with Alginate and Effect of Capsules on Rheological Properties and Stability of an Oil-in-Water Emulsion Model Food - Bautista Villarreal, Minerva; Castillo Hernández, Sandra Loruhama; López Uriarte, Salvador; Barrón González, María Porfiria (Polish Journal of Food and Nutrition Sciences, 2023)
Alginate encapsulation is a viable alternative for the preservation of probiotics along the gastric route or within a food product during its shelf life. Furthermore, co-encapsulation with a vegetal material could act as a prebiotic and enhance the viability of the encapsulated probiotic. The rheological properties of dressing-type foods could be altered by adding an ingredient that would affect the quality of the final product. In this investigation, alginate beads loaded with Lactiplantibacillus plantarum and beetroot extract were obtained by two methods (emulsification and extrusion). They were characterized by size and morphology, encapsulation efficiency, and bacteria viability under simulated gastrointestinal conditions. Finally, they were added in an oil-in-water emulsion model food for which rheological properties and probiotic survival were monitored. The encapsulation efficiency ranged from 86.4 to 88%. Morphology and size of capsules varied depending on the method of encapsulation applied. No significant changes were evidenced in the rheological properties of the model food; the viscosity, the particle size (d3,2), and the coalescence rate remained stable after the addition of the capsules. Survival of L. plantarum was significantly higher in the capsules with beetroot extract. These results suggest a prebiotic effect conferred by the beetroot extract when co-encapsulated. It is worth mentioning that the incorporation of capsules with beetroot extract does not cause any destabilization of the model food.